SUGARCANE FARMERS IN EAST JAVA: INSTITUTIONAL ARRANGEMENT PERSPECTIVE - Baksh, Rukavina; Yustika, Ahmad Erani (Journal of Indonesian Applied Economics, 2008)
In 1930’s decade, Indonesia was recognized as one of the great sugarproducing  countries  in  the world.  Sugarcane  is mostly  grown  in  East  JavaProvince. This area contributes about 40 percent to national sugar production.However, the performance of sugar industry in East Java during the last decadehas declined, which is shown in decreasing volume of production and increasingsugar price. This study utilized the analysis of institutional arrangement to identifythe problems.  In details,  this research empirically compared contract  (credit)and  non-contract  (non-credit)  sugarcane  farmers.  This  research  found  thatinstitutional arrangements between economic actors  in sugar industry are notsuitable, especially for sugarcane farmers. In the case of share-yield system, dueto lack of institutional arrangements, sugarcane farmers rarely get any molassesshare from sugar mill. Another, in the credit point of view, cooperative usuallybears on  sugarcane  farmers  the higher  interest  from  legal rules. Lastly, whencooperative gives aid in the form of seed/fertilizer to sugarcane farmers, it is doneintransparently.Keywords: institutional arrangements, contract systems, sugarcane farmers, EastJava, Indonesia